Recovery of Coilia nasus resources after implementation of the 10-year fishing ban in the Yangtze River: implied from the Yangtze River Estuary and its adjacent sea areas - Wang, Shuyan; Xiong, Ying; Zhang, Hushun; Song, Dade; Wang, Yanping; Ge, Hui; Zhang, Chengbin; Liang, Long; Zhong, Xiaming (Frontiers in Marine Science, 2024)
Introduction The implementation of the 10-year fishing ban in the Yangtze River has provided a crucial opportunity for the recovery of rare and endangered diadromous species, such as Coilia nasus. Methods In this study, we utilized electronic length–frequency analysis (ELEFAN) and length-based Bayesian biomass estimation (LBB) method to fit the body length data of C. nasus from the Yangtze River Estuary and its adjacent sea areas before and after the fishing ban (2019-2023), and the resource changes of C. nasus population were evaluated. Additionally, combined the catch production monitoring data from 2020 to 2022, we comprehensively analyzed the impact of the Yangtze River fishing ban on the recovery of C. nasus resources. Results The results showed that: (1) The proportion of quantity, weight and occurrence frequency of C. nasus in catches showed a significant increasing trend year by year. (2) 4,994 C. nasus were caught from 2021–2023, with body lengths ranging from 13–410 mm. In 2023, the average body length and weight of C. nasus had increased by 39.93% and 133.89%, respectively, from those in 2021. (3) ELEFAN estimated that the growth parameters after fishing ban, including asymptotic length, growth coefficient, and the theoretical age at length zero, were determined to be 42.92 cm, 0.43 year-1, and -0.31 year, respectively. The total mortality rate, fishing mortality rate, and exploitation rate were determined to be 1.47 year-1, 0.79 year-1, and 0.54, respectively. (4) LBB estimated that the relative fishing mortality of C. nasus before the fishing ban increased from 1.22 in 2019 to 2.65 in 2020, while the relative biomass decreased from 0.34 to 0.22. After the fishing ban, the relative fishing mortality decreased from 0.85 in 2021 to 0.06 in 2023, and the relative biomass increased from 0.26 in 2021 to 0.90 in 2023, with a significant increase in 2022, indicating a clear recovery trend in C. nasus resources. Discussion By quantifying the resource characteristics of C. nasus before and after the 10-year fishing ban on the Yangtze River, this research revealed the impact of the ban and provided a reference for future systematic evaluations of the C. nasus population.